PENGARUH PEMBERIAN REWARD, INSENTIF DAN MOTIVASI TERHADAP KINERJA KARYAWAN RUMAH SAKIT SILOAM MEDA - Hasan, Junaidi (Ekonomika : Jurnal Ekonomi dan Pembangunan, 2022)
The purpose of this research is to determine rewards, incentives and motivation for employee performance. The method used is descriptive method, this type of research is quantitative data, primary data obtained through questionnaires. The population in this study was all 73 employees in the company. The sample used is a saturated sampling technique where the entire population will be used as a sample. The analysis technique used is multiple linear analysis. Test results show that partially or simultaneously reward, incentive and motivation variables influence employee performance at Siloam Dhirga Surya Hospital Medan